Empowering ASEAN Regional Integration Through European Union Model Under International Law (South China Sea Case Study) - Mirza, Isroni Muhammad Miraj; Subandi, Agit Yogi; Pratama, Andre Arya (Indonesian Perspective, 2024)
Regional integration in ASEAN has been a delicate and ongoing issue over the years. Such goal is hard to achieved due to the ASEAN Way, including its “Non-Intervention Principle” which consequently has transformed ASEAN into a governmental driven regional institution, instead of supranational organization. The case of South China Sea is one prime example of how incompetent ASEAN is in dealing with regional security threat inflicting its member states. This conflict poses an even larger threat if it is not tackled seriously. This paper uses Juridical normative method by looking at international legal instruments in analyzing ASEAN’s empowerment for regional integration to tackle regional security matters. By looking at EU Model as a source of reference. This paper shows ASEAN-EU relations has grown significantly and many believe ASEAN has the capacity to transform like the EU in the future. There are a number of international legal instruments which under serious amendment, can transform ASEAN towards that goal, particularly in helping to deal with the never ending South China Sea conflict.